THE GAME SYSTEM OF PRE-SCHOOL H A EDUCATION BERIS H STRATEGY - Rustamova , M.E. (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Play is fundamental to children's development, encompassing physical, mental, social, and emotional health. It serves as a critical avenue for fostering overall well-being and prosperity in early childhood education. Specific Background: Despite the recognized importance of play, many children, especially those from deprived backgrounds, face barriers that hinder their access to play opportunities. This lack of engagement can lead to significant social and emotional challenges as they grow. Knowledge Gap: Existing research has often overlooked the interplay between play and the various dimensions of child development, particularly in the context of preschool education. There is a need for a deeper understanding of how play strategies can be systematically integrated into educational frameworks to enhance developmental outcomes. Aims: This study aims to investigate the game system of preschool education, focusing on the implementation of a H A (Holistic Approach) education strategy that prioritizes play as a central learning tool. Results: Findings reveal that integrating a structured play-based approach significantly improves children's physical, mental, social, and emotional skills, offering them better coping mechanisms for future challenges. Novelty: This research introduces a comprehensive framework for incorporating play into preschool curricula, highlighting its multifaceted benefits and the necessity of creating inclusive environments that support play for all children. Implications: The implications of this study are profound, suggesting that educational policymakers and practitioners should prioritize play in preschool settings to foster holistic development, particularly for marginalized populations. This approach not only enhances individual child outcomes but also contributes to the development of resilient communities.